Using compound trace fossils to unravel complex behavioral strategies of worm-like tracemakers traversing transitional environments in the early Paleozoic - Yi-ting Liu; Qing-yang Xu; Yilong Liu; Li-Jun Zhang; Ruo-ying Fan; Yi-ming Gong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Investigation of Near-Surface S-Wave Velocity Structure beneath the Epicenter and adjacent Area of the Jishishan Earthquake by using the Receiver Function - Fan-chang Meng; Ruo-ge Xu; Hui Sun; Bo Li; Yun Long (Applied Geophysics, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

A compact on-chip microsensor for dual-channel measurement of potassium and creatinine in whole blood - Haijing Tian; Ruo Wu; Qi Lv; Jie Shi; Xiaoqin Guo; Duo Li; Chunli Liu; Qi Li; Weijia Zheng; Haojun Fan; Xuexin Duan; Qiannan Xue (Analytica Chimica Acta, 2025)

Dual-directional regulation of extracellular respiration in Shewanella oneidensis for intelligently treating multi-nuclide contamination - Xin-Lu Cai; Xuan Yao; Li Zhang; Yu-Han Chai; Xuan Liu; Wen-Wen Liu; Ruo-Xi Zhang; Yang-Yang Fan; Xiang Xiao (Journal of Hazardous Materials, 2024)

Link Brain-Wide Projectome to Neuronal Dynamics in the Mouse Brain - Xiang Li; Yun Du; Jiang-Feng Huang; Wen-Wei Li; Wei Song; Ruo-Nan Fan; Hua Zhou; Tao Jiang; Chang-Geng Lu; Zhuang Guan; Xiao-Fei Wang; Hui Gong; et al. (Neuroscience Bulletin, 2024)
Knowledge about the neuronal dynamics and the projectome are both essential for understanding how the neuronal network functions in concert. However, it remains challenging to obtain the neural activity and the brain-wide projectome for the same neurons, especially for neurons in subcortical brain regions. Here, by combining in vivo microscopy and high-definition fluorescence micro-optical sectioning tomography, we have developed strategies for mapping the brain-wide projectome of functionally relevant neurons in the somatosensory cortex, the dorsal hippocampus, and the substantia nigra pars compacta. More importantly, we also developed a strategy to achieve acquiring the neural dynamic and brain-wide projectome of the molecularly defined neuronal subtype. The strategies developed in this study solved the essential problem of linking brain-wide projectome to neuronal dynamics for neurons in subcortical structures and provided valuable approaches for understanding how the brain is functionally organized via intricate connectivity patterns.

Spray of water-in-oil emulsified heavy oil with high water content - Ruo-Fan Shi; Yu-Feng Xi; Li-Tao Wang; Hong-Jun Lu; Xiao Zhang; Xin-Yue Zhang; Zi-Bin Huang; Pei-Qing Yuan (Chemical Engineering Journal, 2024)

Deciphering the formation of granules by n-DAMO and Anammox microorganisms - Zhi-Cheng Zhao; Ruo-Lin Li; Sheng-Qiang Fan; Yang Lu; Bing-Feng Liu; De-Feng Xing; Nan-Qi Ren; Guo-Jun Xie (Environmental Research, 2024)

Optimizing the rate of straw returning to balance trade-offs between carbon emission budget and rice yield in China - Ruo-Chen Li; Yu-Gang Tian; Fan Wang; Yuan-Feng Sun; Bai-Jian Lin; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang; Zhi-Yu Xu (Sustainable Production and Consumption, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Manganese doped hollow cobalt oxide catalysts for highly efficient oxygen evolution in wide pH range - Jing-Yi Xie; Fu-Li Wang; Xue-Jun Zhai; Xin Li; Yu-Sheng Zhang; Ruo-Yao Fan; Ren-Qing Lv; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Arsenic induced autophagy-dependent apoptosis in hippocampal neurons via AMPK/mTOR signaling pathway - Yao Chen; Xudan Liu; Qianhui Zhang; Huanhuan Wang; Ruo Zhang; Yanhong Ge; Huning Liang; Wanying Li; Juanjun Fan; Huimin Liu; Zhengyang Lv; Wenting Dou; et al. (Food and Chemical Toxicology, 2023)

Fermented foods and metabolic outcomes in diabetes and prediabetes: A systematic review and meta-analysis of randomized controlled trials - Xiao-Feng Zhang; Yue Qi; Yong-Ping Zhang; Jin-Lan Deng; Xiao-Li Chen; Ruo-Nan Li; Qi-Lun Zhou; Jian-Ming Fan (Critical Reviews in Food Science and Nutrition, 2023)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Currents shaped the genetic structure of Tridentiger barbatus (Günther 1861) along the Chinese coast - Jiehong Wei; Min-Yun Liu; Jen-Chieh Shiao; Fan Li; Jinquan Yang; Yoshiyuki Iizuka; Bin Kang; Ruo-Shan Tseng; Huan-Jie Shao; Te-Yu Liao (Frontiers in Marine Science, 2022)
The modern coast of China is characterized by complicated hydrology, which might be a potential factor shaping genetic structure of marine organisms. Tridentiger barbatus is a widespread benthic goby in coastal China whose range expansion might depend on larval dispersal in its spawning season. We explored the genetic structure of T. barbatus and its interrelationships with coastal currents, planktonic larval duration, and Pleistocene climate fluctuations. Genealogies of Cytb , Rh , and RAG1 reveal two lineages in T. barbatus , namely the southern and northern lineages. The southern lineage is distributed through the South China Sea to the South Yellow Sea but is absent from the North Yellow Sea and Bohai Sea. The HYCOM average flow field indicates an eddy between the North and South Yellow Seas, which might cause larval retention and limit dispersal of the southern lineage into the North Yellow Sea and the Bohai Sea. The northern lineage is distributed through the South Yellow Sea to the Bohai Sea but is absent from the South China Sea and East China Sea. The distribution of the northern lineage fits the eastward deflection of the Yellow Sea Coastal Current at the boundary of the East China Sea and South Yellow Sea, which might limit southward larval dispersal of the northern lineage into the East China Sea. We also uncovered two Cytb haplotype groups within the southern lineage, namely groups A and B, whose distributions might be shaped by the northward Taiwan Strait Current. The coincidence between the genetic structure of T. barbatus and the coastal currents and eddies strongly implies significant roles of larval dispersal and current transportation in shaping the genetic structure of T. barbatus . In addition, significant isolation by distance is found in the southern lineage, which coincides with its short planktonic larval duration (20–30 days). The inference on divergence time suggests that the observed lineages and haplotype groups in T. barbatus originated in the Pleistocene glaciations. Therefore, the coastal currents, planktonic larval duration, and historical glacial isolation are proposed as important factors shaping the genetic structure of T. barbatus .

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

First report of cucumber mosaic virus infecting bahizi (Angelica dahurica) in China - Ruo-Fan Wei; Wan-Long Ding; Yong Li; Rong Wang (Journal of Plant Pathology, 2020)